Tobacco and Tobacco-Related Oral Lesions: Current Concepts and Updates (Academia Journal of Medicine, 2026)
Tobacco use remains a leading preventable cause of morbidity and mortality worldwide and is strongly linked to numerous oral mucosal lesions, ranging from reversible keratotic changes to Oral squamous cell carcinoma. Both smoked and smokeless tobacco damage oral tissues through chemical, thermal, and immunologic mechanisms. Emerging products such as electronic cigarette and heat-not-burn device present new challenges for dental professionals. Tobacco-related lesions include smoker’s palate, tobacco pouch keratosis, oral leukoplakia, erythroplakia, oral submucous fibrosis, and OSCC, many classified as oral potentially malignant disorders. Early detection is essential to reduce malignant transformation and improve prognosis. Advances in molecular biology and salivary diagnostics, including biomarker and immunologic testing, have enhanced early identification. Dental professionals play a vital role in screening, patient education, tobacco cessation counseling, and timely intervention to improve overall oral and systemic health outcomes.
Keywords: Tobacco, Oral potentially malignant disorders, Oral leukoplakia, Oral submucous fibrosis, Smokeless tobacco, Oral cancer